A new species of Dendrobium (Orchidaceae: Epidendroideae: Malaxideae) described from previously perplexing specimens of the Seidenfaden collection - Phueakkhlai, Orporn; Suddee, Somran; Hodkinson, Trevor R.; Sungkaew, Sarawood; Pedersen, Henrik Æ. (Phytotaxa, 2019)
A previously unrecognized species represented by six spirit samples in the collection of the late Gunnar Seidenfaden, pioneering Danish explorer of the Thai orchid flora, is newly described. It is evident that Seidenfaden was perplexed by the material, as three different species names can be observed on the labels (often accompanied by question marks or indications such as “probably”): D. fimbriatum, D. gibsonii and D. chryseum. In our view, the new species has the strongest morphological resemblance to D. fimbriatum, but it differs in characters of the stems, leaves, lateral sepals, petals and labellum. We describe the new species as D. perplexum, the epithet referring to the previously perplexing properties of the material. So far, D. perplexum is only known from NE Thailand, but as the confirmed Thai localities are close to the Laotian border, future finds in Laos might be expected.